Role of Haematological Parameters and Oxidative Stress in Malarial Patients - Saleem Akhtar, Zainab Iqbal, Iqra Shahnwaz (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Malaria has been in existence for so long and is responsible for worrisome health and economic impact in different parts of the world. Objectives: The main objective of the study is to find the haematological parameters and oxidative stress in malarial patients. Material and methods: This cross sectional study was conducted in DHQ Hospital Bhakkar during 2020 to 2021. The data was collected from 200 male and female patients. Participants remembered for the review were under-5-year-old youngsters, either conceded in the kids’ ward or going to any center on short term premise. Results: The information was gathered from 200 malarial patients. There was a genuinely huge decrease in hemoglobin (p<0.005), platelet count (p<0.001) and all out leukocyte count (p<0.001) levels in patients with malaria contrasted with patients without the sickness. The level of neutrophils in the subjects with malaria was fundamentally higher (p<0.005) than in the non-malaria bunch. Conclusion: It is inferred that Low platelet count is a trademark finding of malarial contamination and thrombocytopenia might be more normal than weakness in intense malaria disease.